Un Paisaje Holandés = A Dutch Landscape - La Casa Encendida, Madrid (Madrid : Roma Publication, 2012)
Ader, Bas Jan; Beckers, Feiko; Boelens, Gwenneth; Boezem, Marinus; Brouwn, Stanley; Dibbets, Jan; van Elk, Ger; Houkema, Sharon; van Kreij, Marijn; Mater, Katja; Nuur, Navid; in 't Veld, Martijn
Publicatie n.a.v. tentoonstelling "A Dutch Landscape / Un Paisaje Holandés" in La Casa Encendida te Madrid, 02.02.2012 - 08.04.2012
boek